Methodology for the phenotypic evaluation in Guazuma crinita trees in Ucayali, Peru - Revilla-Chávez, Jorge Manuel [UNESP]; López-Galán, Edinson Eduardo; Gonzales-Alvarado, Antony Cristhian; Sáenz-Ramírez, Lyanna Hellen; Mori-Vásquez, Jorge Arturo; Rojas-Mego, Krystel Clarissa; Abanto-Rodríguez, Carlos; Sebbenn, Alexandre Magno [UNESP] (Universidade Federal de Santa Maria, 2023)
The objective of this study was to present a methodological tool for the phenotypic evaluation in progeny tests of Guazuma crinita in producer plots of the Aguaytía river basin, Ucayali, Peru, which allows field technicians to standardize the morphological evaluation criteria of trees in forest plantations. Therefore, the phenotypic traits were evaluated for plant height (m), diameter at the height of the base (cm), number of branches, number of rings, stem form, branch orientation, presence and quantity of leaves. The heritability and genetic and phenotypic correlations between traits were also estimated. Therefore, 32 morphological categories were plotted based on the significant correlations (p≤ 0.05) shown between the place of planting, the stem form, the orientation of the branches and the presence of leaves. For the same reason, the progeny showed low morphological patterns, being a low factor of phenotypic variability. It is concluded that the correlations between the biometric and morphological traits evaluated, allowed to validate the phenotypic evaluation procedures of Guazuma crinita progeny tests at 36 months of age.
Metodologia para avaliação fenotípica de árvores de Guazuma crinita em Ucayali, Peru
Keywords: Aguaytia Basin; Amazon; Bolaina blanca; Progeny test